2014
DOI: 10.1007/s11033-014-3766-5
|View full text |Cite
|
Sign up to set email alerts
|

The early life origin theory in the development of cardiovascular disease and type 2 diabetes

Abstract: Life expectancy has been examined from a variety of perspectives in recent history. Epidemiology is one perspective which examines causes of morbidity and mortality at the population level. Over the past few 100 years there have been dramatic shifts in the major causes of death and expected life length. This change has suffered from inconsistency across time and space with vast inequalities observed between population groups. In current focus is the challenge of rising non-communicable diseases (NCD), such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…These three factors -maternal nutrition, smoking, and low SES -are all linked with low birthweight [10,20,23], a correlation further supported by a study concerning smoking [24], which shows that low SES and low birthweight are often found together with preterm birth [9,25]. In addition, smoking and low SES are known risk factors for preterm birth [26,27].…”
Section: Background Developmental Origins Of Adult Diseasementioning
confidence: 66%
See 1 more Smart Citation
“…These three factors -maternal nutrition, smoking, and low SES -are all linked with low birthweight [10,20,23], a correlation further supported by a study concerning smoking [24], which shows that low SES and low birthweight are often found together with preterm birth [9,25]. In addition, smoking and low SES are known risk factors for preterm birth [26,27].…”
Section: Background Developmental Origins Of Adult Diseasementioning
confidence: 66%
“…unknown father, mother pregnant before age 17, permanent disability, prison record, prior record of children in foster care, emotional and/or physical problems caring for the baby), infant symptoms (eating disturbances; sleeping problems; excessive crying) [75]. Infants at high psychosocial risk are often overrepresented among preterm infants, since low SES as well as teenage pregnancy are risk factors for preterm childbirth [27,28]. Ten-year old children whose mothers displayed symptoms of depression since childbirth, had increased levels of glucocorticoids and an increase in amygdala volume [76].…”
Section: Infants At High Psychosocial Riskmentioning
confidence: 99%
“…Also, although DOHaD research has linked low birthweight with both adult cardiovascular and metabolic health, 23 these effects may need to be distinguished for perinatal outcomes – it has long been known that maternal glucose is associated with higher birthweight, 24 and higher lipids have been associated with lower gestational age. 25 Animal work indicates the possibility of transgenerational or multigenerational influences on health, although the research is still in its early stages: maternal diet in generation 1 has been found to predict adiposity in mice through generation 3 and sometimes 4.…”
Section: Discussionmentioning
confidence: 99%
“…An example that is easy to understand is habitual smoking that affects the DNA methylation states of the smoker (Breitling et al 2011; Alegria-Torres et al 2011). In addition, epigenetic causes have been suggested for type-2 diabetes, atherosclerotic heart diseases and various kinds of cancers (Lindblom et al 2015;Sandoval and Esteller 2012;Simo-Riudalbas and Esteller 2014). However, malformation and diseases are not directly related to evolution, and we will therefore not discuss these problems further.…”
Section: Two Pathways To Phenotypementioning
confidence: 99%